The Effect of Transformational Leadership on The Development of Human Resources, Creativity and Performance of Members (Study of the Bajawa Creative Women Community in the Local Food Business Sector, Ngada Regency, East Nusa Tenggara) - Agnes Yunita Dea; Hamidah Nayati Utami; Arik Prasetya (Sekolah Pascasarjana Universitas Brawijaya, 2019)
This research is based on the background of the influence of the existence of transformational leadership on the development of human resources, creativity and performance of members of the Bajawa creative women's community. This study uses independent variables namely transformational leadership style (X), intervening variables namely human resource development (Z1) and creativity (Z2) and the dependent variable is performance (Y). Data collection in this study was using a questionnaire distributed to 60 respondents using saturated sample techniques. While the analysis technique is done using Partial Least Square. The results of this study indicate that transformational leadership style has a positive and significant effect on the development of human resources, creativity and performance.